The Area of Foramen Magnum Its Applicability for Sex Determination - Günay, Yasemin; Altınkök, Muzaffer; Çağdır, Sadi; Sarı, Hüseyin (The Bulletin of Legal Medicine, 1998)
In unidentified skeletons, sex determination is rarely easily and correctly performed. In explosions, warfare and other mass disasters like aircraft crashes, identification is also difficult because of skeletal fragmentation. In the present study we attempted to evaluate whether the area of the foramen magnum is a useful criterion for sex determination in fragmented skulls. In a total of 146 skeletons ( 121 males and 25 females ) the longest and the shortest diameter of the foramen magnum was measured; the circle area was determinated with the mean of the diameters as the radius. Foramen magnum areas of 922 qmm and greater were predominantly appointed to male, values lower than 821 qmm predominantly to female skulls. Values greater than 821 qmm and lower than 922 qmm form the group of unidentified skulls. 69 % of males were found to be within 922 qmm ± 1 SD (122 qmm), 68 % of females within 821 qmm ±1 SD (127 qmm). Key words: Foramen magnum, sex determination.